Intimate Partner Homicide in California, 1987-2000 - Wells, William ([Verlag nicht ermittelbar], 2003)
Since 1976, the United States has witnessed a steady and precipitous decline in intimate partner homicides. This study builds on the work of Dugan et al. (1999, 2000) and Browne and Williams (1989) by examining, in greater detail, the relationship between intimate partner homicide and gender, race, criminal justice system response, and domestic violence services. Specifically, the study examines the net effect of criminal justice system response and federally-funded domestic violence shelters on victimization of white, African American, and Hispanic males and females. This study used aggregated data from the 58 counties in California from 1987 to 2000. Homicide data were gathered by the State of California Department of Justice, Criminal Justice Statistics Center. Data on domestic violence resources were obtained from the Governor's Office of Criminal Justice Planning, Domestic Violence Branch, in the form of detailed reports from domestic violence shelters in the state. Based on these records, the researchers computed the number of federally-funded shelter-based organizations in a given county over time. Data on criminal justice responses at the county level were gathered from the State of California Department of Justice, Criminal Justice Statistics Center. These data included domestic violence arrests and any convictions and incarceration that followed those arrests. The researchers disaggregated these criminal justice system measures by race and gender. In order to account for population differences and changes over time, rates were computed per 100,000 adults (age 18 and older).